A comparison of frequency of medical interventions and birth outcomes between the midwife led unit and the obstetric unit in low-risk primiparous women - Anita Prelec; Ivan Verdenik; Angela Poat (Nurses and Midwives Association of Slovenia, 2014)
Introduction: The purpose of this national research was to compare birth, maternal and newborn outcomes in the midwife led unit and the obstetric unit to ascertain whether a midwife led unit reduced medicalisation of childbirth. Methods: A prospective observational case-control study was carried out in Ljubljana Maternity Hospital in the period May - August 2013. The sample comprised 497 labouring women; 154 who attended the midwife led and 343 who attended in the obstetric unit, both matching the same inclusion criteria: low risk primiparous; singleton term pregnancies, normal foetal heart beat, cephalic presentation; spontaneous onset of labour. The primary outcome was the caesarean section rate. Chi-square test was used to compare medical interventions and birth outcomes. Results: Women in the midwife led unit had statistically significant higher spontaneous vaginal births (p < 0.001), less augmentation with oxytocin (p < 0.001), less use of analgesia (p < 0.001), less operative vaginal deliveries (p < 0.001) and less caesarean sections (p < 0.001), lower rates of episiotomy (p < 0.001) and more exclusively breastfed (p = 0.002). Discussion and conclusion: These significant findings showed that in the midwife led unit fewer medical interventions were used. For generalisation of the findings more similar studies in Slovenia are needed.